Phytochemical analysis of Brachiaria grasses from Bowen University dairy farm and molecular docking of constituents with insulin-like growth factor binding protein - Peluola Olujide Ayeni; Blessing Ariyo Obafemi; Gbadebo Emmanuel Adeleke; Akingbolabo Daniel Ogunlakin; Adeshina Isaiah Odugbemi; Ademola Olabode Ayeleso; Oluwafemi Adeleke Ojo (Informatics in Medicine Unlocked, 2023)
Objectives: Brachiaria spp. are nutritious plants that are widely consumed by cows to enhance milk productivity. This study was designed to evaluate the qualitative and quantitative phytochemical constituents of three Brachiaria grasses which are Brachiaria gayana, Brachiaria sabia, and Brachiaria marandu. Methods: The phytochemical components of the three selected Brachiaria grasses were investigated via qualitative and quantitative phytochemical screening via HPLC analysis and the In silico study was also carried out on the major bioactive compound contained in the three Brachiaria species and their interactions with insulin-like growth factor binding protein 3 (IGFBP-3), which inhibit milk production. Key findings: The results revealed that the three Brachiaria species contained antioxidants and other bioactive compounds with Brachiaria gayana exhibiting a higher total flavonoid content than Brachiaria sabia and Brachiaria marandu, while Brachiaria marandu exhibited higher total phenolic content and other bioactive compounds than Brachiaria gayana and Brachiaria sabia. Rhamnetin, Quercetin, and Kaempferol showed the most favourable binding free energies with IGFBP-3 (values of −34.27, −36.40, and −36.65 kcal/mol, respectively). Residues Gln97, Pro98, Gly101, Arg126, and Tyr128 are elucidated as pivotal contributors, facilitating hydrogen bonding and hydrophobic interactions with the ligands. Conclusion: This study therefore reveals that the consumption of Brachiaria grasses reduced the effect of insulin-like growth factor binding protein 3 (IGFBP-3), favouring lactation and milk production in cows.